Вироби зі скла з розкопок давнього Чорнобиля - Журухіна, О.Ю. (Археологія і давня історія України, 2016)
У статті розглянута морфологічна та технологічна характеристика скляних виробів, знайдених під час археологічних досліджень 2013—2015 рр. у м. Чорнобиль. Асортимент знахідок складають вироби масового виробництвa — посуд та прикраси, серед яких зустрічаються предмети як місцевого, давньоруського виробництва, так і імпорт (візантійський та середньоазійський). Стеклянные изделия, найденные во время археологических исследований в 2013—2015 гг. в Чернобыле, представлены посудой и украшениями. Большинство из находок дошло до нас в виде фрагментов и осколков. Посуда немногочисленна — несколько венчиков, стенок и донышек из светло-желтого прозрачного стекла древнерусского производства XI— XIII вв. Две находки можно отнести к импорту: стенку сосуда со следами росписи эмалью и, вероятно, крышечку для флакона, который мог использоваться в парфюмерно-аптекарских целях. The paper includes review of glassware finds from archaeological excavations in Chornobyl (vessels and jewelry). Most of them are fragments of glass. Vessels were produced of thin light yellow Old Rus glass. There are whisks, walls and bedplates. Some of finds are pieces of imported vessels: painted with enamel fragment of vessel wall and, presumable and bottle cover. The jewelry is distributed into two groups of finds: bracelets and beads. Among glass objects the most numerous are bracelets (which is over 77,5 % of all glass finds or 394 items). The bracelets were produced of transparent or semitransparent colored glass and distributed into 9 types according to the shape of cross-sections. The morphological characteristic of most of bracelets shows to their Old Rus origin. Some items are of Byzantine origin. For example, there are bracelets, made of deep blue transparent or semitransparent glass. Other glass finds are beads (more than 19 %), distributed into three sub-groups: mono, polychrome and beads with metal foil. Most of them were produced by winding of glass mass around of the pivot of the tool, which was typical for Byzantine and Old Rus glass manufacturing.